2018
DOI: 10.5194/amt-11-5471-2018
|View full text |Cite
|
Sign up to set email alerts
|

Retrieval of snowflake microphysical properties from multifrequency radar observations

Abstract: We have developed an algorithm that retrieves the size, number concentration and density of falling snow from multifrequency radar observations. This work builds on previous studies that have indicated that three-frequency radars can provide information on snow density, potentially improving the accuracy of snow parameter estimates. The algorithm is based on a Bayesian framework, using lookup tables mapping the measurement space to the state space, which allows fast and robust retrieval. In the forward model, … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
69
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
1
1
1

Relationship

2
5

Authors

Journals

citations
Cited by 58 publications
(70 citation statements)
references
References 55 publications
1
69
0
Order By: Relevance
“…These results indicate that, at least as the retrieval is configured here, triple-frequency radar measurements are insufficient to constrain a retrieval of the density factor. This is consistent with the results of Leinonen et al (2018), wherein the retrieved 20 prefactor of the particle mass-size relation was relatively insensitive to the triple-frequency radar measurements. Instead, the mean Doppler velocity provides an effective constraint on the density of rimed snow, as in Mason et al (2018).…”
Section: Triple-frequency Radar Retrievalsupporting
confidence: 91%
See 3 more Smart Citations
“…These results indicate that, at least as the retrieval is configured here, triple-frequency radar measurements are insufficient to constrain a retrieval of the density factor. This is consistent with the results of Leinonen et al (2018), wherein the retrieved 20 prefactor of the particle mass-size relation was relatively insensitive to the triple-frequency radar measurements. Instead, the mean Doppler velocity provides an effective constraint on the density of rimed snow, as in Mason et al (2018).…”
Section: Triple-frequency Radar Retrievalsupporting
confidence: 91%
“…Using groundbased triple-frequency radar measurements alongside in situ measurements of particle properties at the surface, we showed that including variations in the PSD shape permitted more accurate representations of the measured triple-frequency radar The potential to use advanced radar measurements to constrain ice particle properties in retrievals is of significant interest for reducing uncertainties in remote-sensed estimates of ice water content and snowfall, as well as improving understanding of the microphysics of ice and mixed-phase cloud. Two recent studies have used triple-frequency airborne radar measurements to constrain retrievals of ice particle density by modifying the prefactor of the mass-size distribution (Leinonen et al, 2018;Tridon et al, 2019); however, both studies found that triple-frequency radar retrievals were not substantially different from dual-frequency retrievals, suggesting that the problem was over-constrained. An alternative approach to estimating ice particle properties has been to use Doppler velocity as a constraint on particle density (Szyrmer and Zawadzki, 2014a;Mason et al, 2018).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…By exploiting the frequency dependence of the interaction between hydrometeors and microwave radiation (Lhermitte, ), multifrequency radars have the potential to provide improved profiles of precipitation rates and of the microphysical properties of the ice and rain particle size distributions (PSDs). Previously, several multifrequency cloud radar techniques have been proposed to derive precipitating ice (Leinonen et al, ; Mason et al, ; Matrosov, ; Turk et al, ) and rain (Firda et al, ; Mason et al, ; Tridon et al, ) in stratiform systems, but few of them provide a simultaneous description of the ice and rain profile (Gaussiat et al, ; Grecu et al, ; ; Seto et al, ). Three points make such a retrieval challenging: The properties of ice crystals are extremely variable (size, shape, and structure), which makes their microwave scattering properties complex.…”
Section: Introductionmentioning
confidence: 99%